A memetic algorithm for a stochastic lot-sizing and sequencing problem. Issue 3 (2015) - Schemeleva, Kseniya; Delorme, Xavier; Dolgui, Alexandre
Abstract: A stochastic multi-product lot-sizing and sequencing problem is considered. Two kinds of uncertainties are integrated into the model: defectives items due to the machines' imperfections and random lead time because of randomly arising breakdowns and uncertain repair time. There are also sequence-dependent set-up times between two items of different types. The optimization problem is to maximize the probability of overall demand satisfying. In the previous work only the lot-sizing part of the problem was considered (a decomposition approach was used). Here we study the entire problem with sequencing and lot-sizing decisions integrated.